Macroeconomic Impact of Sharia Business Unit of Indonesian Islamic Banking On Liquidity Asymmetric Approach - Hakim, Muadz Abdul; Achsani, Noer Azam; Saptono, Imam Teguh (IAIN Kudus, 2023)
This study aims to determine the impact of macroeconomics on the liquidity of Indonesian Sharia Business Units (UUS). The liquidity in this study uses the Financing to Deposit Ratio (FDR). In contrast, the Macro Factors used are Inflation, Rupiah to Dollar Exchange Rate, BI Rate and Gross Domestic Product (GDP). The method used Nonlinear Autoregressive Distributed Lag (NARDL) method with data from January 2015 - June 2022. The results showed that in the long term, that affect UUS liquidity are Positive Rate, Negative Rate, Positive GDP, and Negative GDP, in the short term Inflation, Exchange Rate, Rate, and GDP are both positive and negative. Results show that UUS liquidity is vulnerable to changes in Indonesia's macroeconomic factors.